„Przemalujemy wszystko”. Opowiadanie kolorem we Fragmentach Agnieszki Woszczyńskiej - ROJEK, PATRYCJA (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
“We’ll repaint it all”. The use of color as a storytelling device in Agnieszka Woszczyńska’s Fragments In her short Fragments Agnieszka Woszczyńska applies film color as a storytelling device. Oscillating between the natural and expressionistic use of color, she builds not only a characters outer world but also an image of the characters unspoken motivations. The article contains a profound color analysis of Fragments that covers such issues as the functioning of ocularcentrism as a film leitmotiv and the appearance of the focalizer in film narration.